2012
DOI: 10.1371/journal.pone.0046909
|View full text |Cite
|
Sign up to set email alerts
|

The Cameroon Mobile Phone SMS (CAMPS) Trial: A Randomized Trial of Text Messaging versus Usual Care for Adherence to Antiretroviral Therapy

Abstract: BackgroundMobile phone technology is a novel way of delivering health care and improving health outcomes. This trial investigates the use of motivational mobile phone text messages (SMS) to improve adherence to antiretroviral therapy (ART) over six months.Methodology/Principal FindingsCAMPS was a single-site randomized two-arm parallel design trial in Yaoundé, Cameroon. We enrolled and randomized HIV-positive adults on ART, aged 21 years and above to receive a weekly standardized motivational text message vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
354
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(366 citation statements)
references
References 23 publications
8
354
1
3
Order By: Relevance
“…Our results are similar to those found by Mbuagbaw et al (2012), who found no impact of weekly motivational SMS reminders on adherence to ART in Cameroon. Similarly, Shet et al (2014) found no impact of an automated interactive telephone reminder system on adherence to ART in India, a socioeconomic context that is similar to Pakistan.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results are similar to those found by Mbuagbaw et al (2012), who found no impact of weekly motivational SMS reminders on adherence to ART in Cameroon. Similarly, Shet et al (2014) found no impact of an automated interactive telephone reminder system on adherence to ART in India, a socioeconomic context that is similar to Pakistan.…”
Section: Discussionsupporting
confidence: 91%
“…Two early trials found an impact of short-message service (SMS)-based interventions on drug adherence to ART for people living with HIV (Lester et al 2010;Pop-Eleches et al 2011) and, based on these findings, a Cochrane systematic review was published, advocating their use (Horvath et al 2012). However, more recent trials using motivational weekly SMS reminders in Cameroon and daily automated voice calls in India, found no impact of these interventions on drug adherence to ART (Mbuagbaw et al 2012;Shet et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The study concluded that phone text messages did not significantly improve adherence to ART in this study. Other types of messaging or longer term studies were recommended [27].…”
Section: Resultsmentioning
confidence: 99%
“…One example of a study employing RCTs to examine the efficacy of mHealth include Watts et al, (2013) who conducted a RCT comparing the delivery modality (mobile phone/tablet or fixed computer) of a cognitive behavioural therapy intervention for the treatment of depression. Other examples based in developing countries can be found in the work of Chang et al, (2011), Hoffman et al, (2010, Jones et al,(2012), Lester et al,(2010); Mbuagbaw et al,(2012), Pop-Eleches et al, (2011), & Zurovac et al, (2011. …”
Section: Factorialmentioning
confidence: 99%